ESG Disclosure's Positive Impact on Financial Performance in Indonesia’s Growth - Nurahman, Dany; Majid, Muhammad Abdul; Hersugondo, Hersugondo (Research Horizon, 2024)
This study evaluates the influence of Environmental, Social, and Governance (ESG) disclosure scores on financial performance, with a particular emphasis on Return on Equity (ROE), across 89 companies listed on the Indonesia Stock Exchange (IDX). Amid growing global attention to sustainable business practices, this research seeks to address the role of ESG in driving economic empowerment and sustainable prosperity within Indonesia’s corporate sector. Utilizing a quantitative approach, this study evaluates firm-level data to uncover the relationship between ESG practices and financial outcomes. The analysis reveals that companies with greater ESG disclosure scores consistently exhibit better ROE performance, signifying that sustainable business practices are not only socially responsible but also financially beneficial. The discussion explores how ESG practices help align corporate strategies with stakeholder expectations, fostering greater transparency, improving operational efficiency, and boosting investor confidence. These findings emphasize the significant role of ESG integration in promoting sustainable development and achieving long-term economic growth in Indonesia. Moreover, the study highlights the importance of regulatory frameworks in fostering robust ESG adoption and encouraging responsible investment practices. This research facilitates the literature by offering empirical evidence of ESG’s financial and societal value in Indonesia, advocating for strengthened ESG initiatives as a pathway to sustainable prosperity.